A meiotic linkage map of the silver fox, aligned and compared to the canine genome - Kukekova, Anna V. (Cold Spring Harbor Laboratory Press, 2007)
A meiotic linkage map is essential for mapping traits of interest and is often the first step toward understanding a cryptic genome. Specific strains of silver fox (a variant of the red fox, Vulpes vulpes), which segregate behavioral and morphological phenotypes, create a need for such a map. One such strain, selected for docility, exhibits friendly dog-like responses to humans, in contrast to another strain selected for aggression. Development of a fox map is facilitated by the known cytogenetic homologies between the dog and fox, and by the availability of high resolution canine genome maps and sequence data. Furthermore, the high genomic sequence identity between dog and fox allows adaptation of canine microsatellites for genotyping and meiotic mapping in foxes. Using 320 such markers, we have constructed the first meiotic linkage map of the fox genome. The resulting sex-averaged map covers 16 fox autosomes and the X chromosome with an average inter-marker distance of 7.5 cM. The total map length corresponds to 1480.2 cM. From comparison of sex-averaged meiotic linkage maps of the fox and dog genomes, suppression of recombination in pericentromeric regions of the metacentric fox chromosomes was apparent, relative to the corresponding segments of acrocentric dog chromosomes. Alignment of the fox meiotic map against the 7.6x canine genome sequence revealed high conservation of marker order between homologous regions of the two species. The fox meiotic map provides a critical tool for genetic studies in foxes and identification of genetic loci and genes implicated in fox domestication.